Capitalism and freedom : problems and prospects - Selden, Richard T. (Charlottesville : University Press of Virginia, 1975)
The present volume consists of papers written for a conference held to honour Friedman Milton. The reader will find a loosely constructed series of essays and discussions of particular trouble spots of contemporary capitalism. Topics were selected on the basis of recent work on economy policy; the introductory chapter provides a brief guide to Friedman's view on economic policy as well as an interpretation.
Includes bibliographical references and index.
hza 21/06/2018
Loans
Keywords: Capitalism; United States